Konsep Tasamuh (Toleransi) Menurut Para Ulama Islam dan Tokoh Barat - M.A Farkhan; Arif Rahman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2023)
The main problem in this research is how the ulama explain tasamuh, both in the Koran and in various Islamic and western figures. In the Tasamuh verses in the Qur'an, the main problem will be divided into sub-problems. The research method used in this research is qualitative research, using a library research approach. This type of research is a type of non-interactive qualitative research, which can also be called analytical research in the form of library research. The approach used is an interpretive approach. The data used is primary data sourced from Tafsir books, and secondary data includes related works and other references that can support research. The results of this research show that tasamuh is an attitude or behavior of a person to allow freedom to others and give truth to differences, be they differences of opinion, differences in beliefs, or differences in responding to every problem in social life, and is a recognition of human rights. and mutual respect between communities. It can also be understood that tasamuh is an open-minded attitude towards other people's principles; tasamuh does not mean someone sacrifices the beliefs or principles they adhere to for the sake of other people's principles. namely, mutual respect in social life